Paper Reviews of Agile Methodology Software Development - bin Mohamad Khairi, Aiman Mudzafar; bin Kamaruddin, Mohamad Zainal; Setyawan Widyarto (Proceedings of the Informatics Conference, 2020)
Abstract –There are many suggestions recently on how to improve the software development process. While many developers continue to control the development process using the traditional methodologies, this Agile Methodology comes around. This new methodology takes the development process to a higher level that creates a new challenge to any specific requirements. A sprightly movement in this new methodology created new practices such as Extreme Programming (XP), SCRUM, Lean Software Development (LSD), Crystal, Kanban and many more. The study of this paper is to identify the major changes and the implications to the industry. Firtsly, the authors will describe the meaning of Agile Methodology, followed by their characteristic, development process and the differences between Agile Methodology and traditional method. Secondly, the authors will explain the differences of the practice in Agile Methodology. Last but not least, the authors will bring the readers to the conclusion of their idea of Agile Methodology which make this methodology produce a major changes in project lifecycle